2016
DOI: 10.1017/ice.2016.304
|View full text |Cite
|
Sign up to set email alerts
|

Oak in Hospitals, the Worst Enemy of Staphylococcus aureus?

Abstract: its emergence as a major community pathogen nationally. 8 The concurrent increase in cases of SSIs caused by MSSA, however, was unexpected. This finding suggests that despite the increase in MRSA, MSSA still plays a large role in causing SSIs. Therefore, preoperative screening for Staphylococcus spp., not just MRSA, may help guide preoperative antibiotic selection, skin preparation, and postoperative wound care to minimize the risk of infection with either of these organisms. 9 The predominance of gram-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 6 publications
2
35
0
4
Order By: Relevance
“…The results of this study regarding the antimicrobial activity of wood material are supported by the previous publications reporting that different woods, including oak [ 15 ], larch [ 1 ], pine [ 2 ], spruce [ 13 ], beech, and fir [ 3 ], have antimicrobial properties against various isolates of S. aureus . In this study, however, the antimicrobial activity of wood material was very low against A. baumannii , as compared to S. aureus .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The results of this study regarding the antimicrobial activity of wood material are supported by the previous publications reporting that different woods, including oak [ 15 ], larch [ 1 ], pine [ 2 ], spruce [ 13 ], beech, and fir [ 3 ], have antimicrobial properties against various isolates of S. aureus . In this study, however, the antimicrobial activity of wood material was very low against A. baumannii , as compared to S. aureus .…”
Section: Discussionsupporting
confidence: 86%
“…Direct disc diffusion method was used as described in earlier studies [ 3 , 15 ]; briefly, the bacterial suspensions adjusted to a density of 0.5 McFarland were inoculated by streaking on Mueller–Hinton agar plates (12 × 12 cm) (BioRad, Marnes La Coquette, France), according to the recommendations of the Antibiogram Committee of the French Society of Microbiology [ 19 ]. The wood discs were then placed directly on the agar.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that bacteria and spores could enter deeper (around 3 mm) in transversal cuttings than in longitudinal cut woods, thus, probably posing lesser threat of recontamination with higher number of microbes. Moreover, the wood better utilizes the antimicrobial potential of extractives in transversal direction [6]. In contrast, the longitudinal cut boards of wood were easier to clean because of shallow and wider openings on surface [34].…”
Section: Porous Structure: Does It Support Microbial Growth?mentioning
confidence: 99%